2017
DOI: 10.1007/s10040-017-1624-y
|View full text |Cite
|
Sign up to set email alerts
|

Polyaxial stress-dependent permeability of a three-dimensional fractured rock layer

Abstract: A study about the influence of polyaxial (true-triaxial) stresses on the permeability of a three-dimensional (3D) fractured rock layer is presented. The 3D fracture system is constructed by extruding a two-dimensional (2D) outcrop pattern of a limestone bed that exhibits a ladder structure consisting of a Bthrough-going^joint set abutted by later-stage short fractures. Geomechanical behaviour of the 3D fractured rock in response to in-situ stresses is modelled by the finite-discrete element method, which can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…[1985] model, appears as the next logical step toward physical realism, albeit a very challenging one [cf. Lei et al ., ]. The main difference between this and earlier studies is that we consider permeability anisotropy and matrix permeability.…”
Section: Discussionmentioning
confidence: 95%
“…[1985] model, appears as the next logical step toward physical realism, albeit a very challenging one [cf. Lei et al ., ]. The main difference between this and earlier studies is that we consider permeability anisotropy and matrix permeability.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, this work studied 2‐D fracture system, and there could be important 3‐D effects. While several studies have investigated fluid flow in stressed 3‐D fracture networks (Garipov et al, ; Lei et al, ; McClure et al, ), the effects of geological stress on tracer transport through 3‐D fracture networks remain to be investigated. A recent study has shown that the Bernoulli CTRW model can capture particle transport through 3‐D fracture networks (Hyman et al, ), and the natural extension of this study will be the effects of geological stress on particle transport through stressed 3‐D fracture networks.…”
Section: Discussionmentioning
confidence: 99%
“…The E‐W striking set that formed in an early stage contains laterally persistent fractures, which tend to arrest the later developed N‐S striking set consisting of short fractures. This natural fracture network exhibiting a hierarchical, ladder pattern has been used as an analog to the subsurface system for studying single‐phase flow, multiphase flow, solute transport, and thermal conductivity (Edery et al, ; Geiger & Emmanuel, ; Geiger et al, ; Lei et al, ; Matthäi & Belayneh, ; Matthäi et al, ). In this paper, we represent the system with a two‐dimensional (2‐D) DFN (Geiger et al, ) and use this fracture network to explore the impact of geological stress on single‐phase flow and transport behavior.…”
Section: Methodsmentioning
confidence: 99%
“…This effect cannot be considered in 2‐D modelings. Hence, as also mentioned by Lei et al (), results from 2‐D models may only provide indicative approximations. It is worth noting that in this study all the fractures were initially assumed to be closed.…”
Section: Discussionmentioning
confidence: 89%
“…Combining the geomechanical behavior of the fracture network with its fluid flow properties, they showed that some particular stress states can reactivate the preexisting fractures and can change the system's permeability. Lei et al () also studied the influence of triaxial stresses on the permeability of a 3‐D fractured rock layer, which was created by extruding a 2‐D outcrop pattern. They considered the influence of stress on the permeability of the fractured rock layer running a decoupled geomecahincal and flow analysis.…”
Section: Introductionmentioning
confidence: 99%